ANÁLISIS LITERARIO SOBRE CRÍTICA PSICOLÓGICA DE LA CONCIENCIA EN LA OBRA RETABLOS DE RAFAEL VICTORINO MUÑOZ (De la Crítica, 2024)
Rafael Victorino Muñoz is a venezuelan author whose work provides a current look of the society, from a critic and even ironic perspective, that implies very specific situations with strong subjective opinion. This article pretends to show elements from the psicologycal critic of the conscience that can be found in one of his most famous works: Retablos, which is composed by different short stories. To stand out these elements, authors like Barthes (1982) and Fernandez (2011), are mentioned as experts in literary analysis andtheories about the conscience, respectively; that way is possible to compare their postulates with the resources used by the writer Muñoz.